Pengaruh Orientasi Kewirausahaan Terhadap Kinerja Usaha Pada Industri UMKM Abon Ikan Di Kota Makassar The Effect of Entrepreneurship Orientation toward Business Performance In Fish Abon SME Industry In Makassar City - Ayu Wulandary (Journal of Food System & Agribusiness, 2017)
Business performance is one of the benchmarks of entrepreneurship orientation so that the concept of entrepreneurship orientation of the entrepreneur is important because it has impacts on business performance. The entrepreneurship orientation is shaped by the five dimensions of innovation: risk-taking, proactiveness, competitive aggressiveness, and autonomy. The objective of this study was to analyze the influence of entrepreneurship orientation on business performance of fish abon SME in Makassar. This research employed a Structural Equation Modeling-Partial Least Square (SEM-PLS) 3.0 tool for quantitative analysis. The results of this study indicated that the influence of entrepreneurship orientation had a positive and significant impact on business performance. It could be observed that t-statistic value was 3,302> 1.96 and p-value was 0.001 <0.05, it meant that any improvement to the business adopting entrepreneurship orientation would improve business performance at fish abon SME in Makassar City.